The effects of childhood maltreatment on brain structure in adults with eating disorders. (21st April 2019) - Monteleone, Alessio Maria; Monteleone, Palmiero; Esposito, Fabrizio; Prinster, Anna; Ruzzi, Valeria; Canna, Antonietta; Aiello, Marco; Di Salle, Francesco; Maj, Mario
Abstract: Objectives: Childhood maltreatment is a non-specific risk factor for eating disorders (EDs). However, so far, no study has assessed the impact of childhood maltreatment on brain structure of adults with EDs. Therefore, we investigated brain area volumes and fibre tract integrity of childhood maltreated (Mal) and non-maltreated (noMal) patients with EDs. Methods: Thirty-six ED women and 16 healthy women underwent an MRI scan, including acquisition of a diffusion tensor imaging (DTI) sequence and a high-resolution T1-weighted scan. ED participants were classified as Mal (18 patients) or noMal (18 patients) according to their childhood exposure to traumatic events assessed by the Childhood Trauma Questionnaire (CTQ). Results: Significantly reduced grey matter volume was detected in the right paracentral lobule and in the left inferior temporal gyrus of Mal patients. DTI analyses revealed reduced white matter integrity in the corpus callosum, internal capsule, posterior thalamic radiation, longitudinal fasciculus and corona radiata of Mal patients. Negative correlations emerged between white/grey matter changes and CTQ emotional and physical neglect scores. Conclusions: These results show that childhood trauma affects the integrity of brain structures modulating brain processes, such as reward, taste and body image perception, which play a fundamental role in the psychopathology of EDs.